2017
DOI: 10.1128/mcb.00547-16
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Tiered Mechanism Enables Localized Cdc42 Signaling during Enterocyte Polarization

Abstract: Signaling by the small GTPase Cdc42 governs a diverse set of cellular processes that contribute to tissue morphogenesis. Since these processes often require highly localized signaling, Cdc42 activity must be clustered in order to prevent ectopic signaling. During cell polarization, apical Cdc42 signaling directs the positioning of the nascent apical membrane. However, the molecular mechanisms that drive Cdc42 clustering during polarity establishment are largely unknown. Here, we demonstrate that during cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This relationship between Cdc42 and apical cargo delivery is well supported by the finding that in 3D MDCK spheroids, Rab11-dependent delivery of apical proteins is required for normal Cdc42 activation (Bryant et al, 2010). Furthermore, reminiscent of the mechanism of Cdc42 polarity in budding yeast, recent work in the Caco-2-derived LS174T-W4 cell line using FRAP experiments has shown that activation of Cdc42 by Tuba leads to a threefold increase in the immobilization of Cdc42 to the apical membrane (Bruurs et al, 2017). This promotes Cdc42 clustering and presumably enables a reaction-diffusion mechanism that is comparable to that operating in budding yeast to determine polarity.…”
Section: Role Of Cdc42 In Regulating Lumen Formationmentioning
confidence: 78%
“…This relationship between Cdc42 and apical cargo delivery is well supported by the finding that in 3D MDCK spheroids, Rab11-dependent delivery of apical proteins is required for normal Cdc42 activation (Bryant et al, 2010). Furthermore, reminiscent of the mechanism of Cdc42 polarity in budding yeast, recent work in the Caco-2-derived LS174T-W4 cell line using FRAP experiments has shown that activation of Cdc42 by Tuba leads to a threefold increase in the immobilization of Cdc42 to the apical membrane (Bruurs et al, 2017). This promotes Cdc42 clustering and presumably enables a reaction-diffusion mechanism that is comparable to that operating in budding yeast to determine polarity.…”
Section: Role Of Cdc42 In Regulating Lumen Formationmentioning
confidence: 78%
“…We previously showed that Cdc42 mobility at the apical membrane is highly regulated via a RhoGDI-dependent and Tuba-dependent mechanism and that this regulation is critical for Cdc42 function [ 5 ]. To test whether Par6A contributes to the regulation of Cdc42 mobility we determined the mobility of constitutively active Cdc42(G12V) at the apical membrane of polarized Ls174T:W4 cells and Par6A k.o.…”
Section: Resultsmentioning
confidence: 99%
“…cells. For this we locally photoconverted Dendra-fused Cdc42(G12V) in the brush border and followed its subsequent loss from the converted region as a consequence of lateral diffusion [ 5 ]. We find that the apical mobility of Cdc42(G12V) is higher in Par6A k.o.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations